# Sum rule of Integration

## Formula

$\displaystyle \int{\Big(f(x)+g(x)\Big)\,}dx$ $\,=\,$ $\displaystyle \int{f(x)\,}dx$ $+$ $\displaystyle \int{g(x)\,}dx$

The integral of sum of functions equals to sum of their integrals is called the sum rule of integration.

### Introduction

Let $f(x)$ and $g(x)$ represent two functions in $x$, then the indefinite integral of each function with respect to $x$ can be written in mathematical form as follows.

$(1)\,\,\,$ $\displaystyle \int{f(x)\,}dx$

$(2)\,\,\,$ $\displaystyle \int{g(x)\,}dx$

The sum of functions is written as $f(x)+g(x)$ in mathematics. The integral of sum of the functions with respect $x$ is written in the following mathematical form in integral calculus.

$\displaystyle \int{\Big(f(x)+g(x)\Big)\,}dx$

According to integral calculus, the integral of sum of two or more functions is equal to the sum of their integrals. The following equation expresses this integral property and it is called as the sum rule of integration.

$\implies$ $\displaystyle \int{\Big(f(x)+g(x)\Big)\,}dx$ $\,=\,$ $\displaystyle \int{f(x)\,}dx$ $+$ $\displaystyle \int{g(x)\,}dx$

The sum rule of indefinite integration can also be extended to sum of infinite number of functions.

$\implies$ $\displaystyle \int{\Big(f(x)+g(x)+\ldots\Big)\,}dx$ $\,=\,$ $\displaystyle \int{f(x)\,}dx$ $+$ $\displaystyle \int{g(x)\,}dx$ $+$ $\ldots$

#### Example

Evaluate $\displaystyle \int{(3+4x)\,}dx$

Now, use the integral sum rule to evaluate the integral of sum of the functions.

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $\displaystyle \int{3\,}dx$ $+$ $\displaystyle \int{4x\,}dx$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+c_1$ $+$ $4\displaystyle \int{x\,}dx$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+c_1$ $+$ $4 \times \Big(\dfrac{x^2}{2}+c_2\Big)$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+c_1$ $+$ $4 \times \dfrac{x^2}{2}+4 \times c_2$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+c_1$ $+$ $\dfrac{4 \times x^2}{2}+4c_2$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+c_1$ $+$ $\require{cancel} \dfrac{\cancel{4} \times x^2}{\cancel{2}}+4c_2$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+c_1$ $+$ $2 \times x^2+4c_2$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+c_1$ $+$ $2x^2+4c_2$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+2x^2+c_1+4c_2$

$\implies$ $\displaystyle \int{(3+4x)\,}dx$ $\,=\,$ $3x+2x^2+c$

### Proof

Learn how to prove the addition law of integration in integral calculus.

###### Math Questions

The math problems with solutions to learn how to solve a problem.

Learn solutions

Practice now

###### Math Videos

The math videos tutorials with visual graphics to learn every concept.

Watch now

###### Subscribe us

Get the latest math updates from the Math Doubts by subscribing us.

A free math education service for students to learn every math concept easily, for teachers to teach mathematics understandably and for mathematicians to share their maths researching projects.